2022
DOI: 10.1111/nep.14014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of imatinib treatment on renal function in chronic myeloid leukaemia patients

Abstract: Background: Recently, multiple epidemiological studies have linked imatinib with the alteration of renal function in chronic myeloid leukaemia (CML) patients. This metaanalysis aimed to summarize the impact of imatinib use on renal function in CML patients.Methods: A systematic search was conducted on MEDLINE and Embase to identify articles assessing the impact of imatinib exposure on renal function in CML patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, the authors reported an increased rate of CTR-CVTs in the imatinib cohort when compared to patients treated with 2G-TKIs [119]. A recent meta-analysis confirmed these data, reporting a significantly higher risk of renal impairment (CKD or AKI) in patients treated with imatinib than other TKIs (RR 2.7 IC 95% 1.49-4.91) [64].…”
Section: Renal Function Impairmentmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, the authors reported an increased rate of CTR-CVTs in the imatinib cohort when compared to patients treated with 2G-TKIs [119]. A recent meta-analysis confirmed these data, reporting a significantly higher risk of renal impairment (CKD or AKI) in patients treated with imatinib than other TKIs (RR 2.7 IC 95% 1.49-4.91) [64].…”
Section: Renal Function Impairmentmentioning
confidence: 84%
“…Renal dysfunction associated with TKIs, especially imatinib and bosutinib [64,65], can further increase cardiovascular risk [66]. Pieces of evidence in the literature have reported this association and several hypotheses have been advanced.…”
Section: Renal Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of diagnosis and management of AKI during cancer therapy should be to mitigate the sequelae of these events on optimal cancer treatment. [137,138] Ribociclib [138,139] 12-60% 20-59% 44-61% ATN, AIN [134], Hypokalemia (21%), Hyponatremia (12%) Hypokalemia (13%), Hyponatremia (9%), Hypercalcemia (7%) Hypokalemia (15%), hypocalcemia (14%), Hyponatremia (15%) PARP INH [140] Olaparib Niraparib Rucaparib 20-30% 20-30% 11-30% [141] HTN (19%) [142] BCR-ABL INH Imatinib [143][144][145] Dasatinib [146][147][148] 6-13%…”
Section: Discussionmentioning
confidence: 99%
“…13 There is a dearth of evidence concerning the effect of imatinib on renal impairment and the incidence of anaemia in patients with CML. 14,15 A few studies have reported imatinib-related renal dysfunction and haematological toxicity. 16 Measuring creatinine concentration is not a reliable test for renal function; glomerulus filtration rate (GFR) estimation is a reliable or more validated assessment tool.…”
Section: Introductionmentioning
confidence: 99%